Kepadatan Mikroalga Mixculture Pada Media POME Skala Laboratorium - Djaingsastro, Aulia Juanda; Manurung, Saroha; Maisarah; Dian, Rahmad; Machrizal, Rusdi (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyse the density of microalgae mixculture cultivated in POME media with varying concentrations and to evaluate the effect of POME concentration on microalgae growth. Microalgae mixculture was cultivated in POME media with three concentration variations, namely 10%, 20%, and 30%. Cultivation was carried out for 15 days with cell density observations every three days using a haemocytometer. The results showed that microalgae density increased over time in all treatments. A POME concentration of 30% produced the highest microalgae density at each observation time, with a maximum density of 12,564 cells/ml on the 15th day, followed by concentrations of 20% and 10% at 11,980 cells/ml and 10,080 cells/ml, respectively. These results indicate that an increase in POME concentration has a positive effect on the growth of microalgae mixculture within the concentration range used. Microalgae density increased with cultivation time in all treatments. A 30% POME concentration resulted in the highest microalgae density, indicating that the higher nutrient availability in POME supports microalgae growth. Thus, POME has the potential to be utilised as an alternative medium for microalgae cultivation as well as an effort to manage palm oil industry wastewater.